Stereotactic radiosurgery in the treatment of brain metastases from gynecologic primary cancer - Johnston, Hannah (J Radiosurg SBRT, 2017)
BACKGROUND: Brain metastases from gynecologic primary cancers are rare events, but they can be a cause of morbidity and mortality when they occur. METHODS: This is a single institution retrospective study on patients with brain metastases from gynecologic primary cancer who received Gamma Knife stereotactic radiosurgery (SRS). Between 2000 and 2013, a total of 33 patients with brain metastases from gynecologic primary including cervical (n=2), endometrial (n=6) and ovarian cancers (n=25) were treated with SRS at our institution. Electronic medical records were reviewed to determine survival, patterns of failure and cause of death. RESULTS: Overall survival at 1, 2 and 5 years for the entire population was 47.1%, 21.7%, and 14.5%, respectively. There was no difference in survival between the primary cancers (log-rank p = 0.33). 36.4% patients died of neurologic death. Local failure at 1 and 2 years for the entire population was 10.4% and 14.3%, respectively. There was no difference in local failure between the primary cancers. Distant brain failure at 1, 2 and 5 years for the entire population was 20.6%, 27.7%, and 31.3%, respectively. On multivariate Cox Proportional Hazards analysis, age was the only predictor of overall survival (HR = 1.03, p = 0.01). Ovarian cancer patients had decreased risk of distant brain failure (HR = 0.17, p=0.005), whereas cervical cancer patients had an increased risk of distant brain failure (HR = 35.7, p = 0.001). CONCLUSIONS: SRS represents a feasible treatment option for patients with brain metastases from gynecologic cancer. Younger age is a positive prognostic factor. Ovarian cancer patients have lower risk of distant brain failure.